Periodontal disease, puerperium and premature childbirth - Maritza Peña Sisto; Reinaldo López Barroso; Rafael Alberto Clavería Clark (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Gingivitis and periodontitis prevail in pregnant women and they are associated among other factors, with the gestational age, reason why an association between the periodontal deterioration and premature childbirth is suggested, which constitute health problems worldwide.   Objective: To identify the frequency and seriousness of chronic inflammatory periodontal disease in newly-delivered women with premature childbirth.   Methods: A descriptive and cross-sectional study of 250 newly-delivered women with premature childbirth of alive newborn and unique gestations was carried out; they were assisted in the maternal hospitals of Santiago de Cuba province, from 2018 to 2022. The analyzed variables were prevalence, type, seriousness and extension of the periodontal disease, depth and bleeding in the survey, as well as loss of clinical insertion. For the analysis of quantitative variables the mean, standard deviation and variation coefficient were used as summary measures; for the qualitative ones, the percentage was used.  Results: Periodontal disease was found in 54.0 % of the patients, with a prevalence of gingivitis (31.0 %), most frequent in its moderated and generalized forms, as well as periodontitis (23.0 %), with superiority in the light and localized ways.   Conclusions: The high frequency of periodontal diseases with advanced forms in the newly-delivered women demonstrates the importance of its prevention and control during pregnancy, due to its possible repercussion in prematurity.